2019
DOI: 10.3390/rs11050483
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Remotely Sensed Lines of Evidence for a Depleting Seasonal Snowpack in the Near East

Abstract: The snow-fed river basins of the Near East region are facing an urgent threat in the form of declining water resources. In this study, we analyzed several remote sensing products (optical, passive microwave, and gravimetric) and outputs of a meteorological reanalysis data set to understand the relationship between the terrestrial water storage anomalies and the mountain snowpack. The results from different satellite retrievals show a clear signal of a depletion of both water storage and the seasonal snowpack i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 97 publications
1
9
0
Order By: Relevance
“…In addition, the increased discharge in early winter resulted in a shift in the timing of the discharge peak (1-3 weeks earlier, February instead of March) compared to the baseline simulations ( Figure 8a). These results are consistent with previous studies (e.g., [13,[86][87][88][89][90]. For instance, the studies related to precipitation and discharge change, based on regional climate scenario simulations over the upper Euphrates-Tigris basin, indicate that shifting in snowmelt timing for the future period would have significant implications on the discharge response ( Figure 8a) and therefore on water management [13,87].…”
Section: Discharge Prediction Under Future Climate Conditionssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the increased discharge in early winter resulted in a shift in the timing of the discharge peak (1-3 weeks earlier, February instead of March) compared to the baseline simulations ( Figure 8a). These results are consistent with previous studies (e.g., [13,[86][87][88][89][90]. For instance, the studies related to precipitation and discharge change, based on regional climate scenario simulations over the upper Euphrates-Tigris basin, indicate that shifting in snowmelt timing for the future period would have significant implications on the discharge response ( Figure 8a) and therefore on water management [13,87].…”
Section: Discharge Prediction Under Future Climate Conditionssupporting
confidence: 92%
“…Another study based on observations from streamflow stations for the same region shows that the peak flow timing shifts earlier because of the snowpack decline for the period of 1970-2010 [89]. In addition, recent remote sensing analysis over the transboundary basins of the Near East region demonstrated that snowpack depletion is highly evident for most of the region [90].…”
Section: Discharge Prediction Under Future Climate Conditionsmentioning
confidence: 98%
“…This water-limited region is largely covered by deserts and shows arid to semi-arid characteristics, which are associated with the domination of subtropical high-pressure system shaped by the descending branch of the Hadley cell (Sahin et al, 2015;Sen et al, 2019). The Taurus and Zagros mountains are parts of the NE's water towers, and due to the presence of snowpack in high-elevation regions (>2,000 m), they feed two important rivers of Mesopotamia, the Euphrates and Tigris (Yilmaz et al, 2019) (Figure 1). According to Viviroli et al (2007), the relative water yield, which is a measure of the disproportionality of mountain runoff to lowland runoff, is high for the Euphrates-Tigris Basin.…”
Section: Introductionmentioning
confidence: 99%
“…Another driver of the increasing aridity is the dwindling snow cover due to the reduction in the snowfall ratio and earlier spring snowmelt in Türkiye. Concerning basins influenced by snow, several studies report a general decrease in snow amounts and increasing snowmelt for Türkiye, implying a contribution that could influence changes in drought indices in the future (Özgür & Koçak, 2019; Sönmez et al, 2014; Yılmaz et al, 2019). For instance, results from multiple remote sensing products showed a strong relationship between significant water loss and snow cover decline between 2002 and 2018 in the Euphrates‐Dicle, Kura‐Aras, Çoruh and Van basins.…”
Section: Discussionmentioning
confidence: 99%